2015
DOI: 10.1017/s2040174415007862
|View full text |Cite
|
Sign up to set email alerts
|

Infant gut immunity: a preliminary study of IgA associations with breastfeeding

Abstract: Secretory immunoglobulin A (IgA) plays a critical role in gut mucosal immune defense. Initially provided by breastmilk, IgA production by the infant gut is gradually stimulated by developing gut microbiota. This study reports associations between infant fecal IgA concentrations 4 months after birth, breastfeeding status and other pre/postnatal exposures in 47 infants in the Canadian Healthy Infant Longitudinal Development cohort. Breastfed infants and first-born infants had higher median fecal IgA concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 26 publications
5
37
0
4
Order By: Relevance
“…Second, breast milk contains multiple bacterial species, now referred to as the milk microbiomes [35] that actively colonize the gut. And third, breast milk contains other bioactive factors such as secretory IgA, which has been shown to alter colonization of the infant gut, protecting it against pathogenic bacteria [36, 37]. None of these factors are present in IF, presumably contributing to the lower diversity index initially observed among IF-fed preterm infants, as well as the more rapid acquisition of microbes, the majority being acquired from the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…Second, breast milk contains multiple bacterial species, now referred to as the milk microbiomes [35] that actively colonize the gut. And third, breast milk contains other bioactive factors such as secretory IgA, which has been shown to alter colonization of the infant gut, protecting it against pathogenic bacteria [36, 37]. None of these factors are present in IF, presumably contributing to the lower diversity index initially observed among IF-fed preterm infants, as well as the more rapid acquisition of microbes, the majority being acquired from the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…87,88 By testing mice either expressing or devoid of Ig receptor mice, it has been shown that maternal sIgA in breast milk stimulates offspring gut microbiota changes that persist and are amplified at adulthood, and blocks translocation of aerobic bacteria, including the pathogen Ochrobactrum antropi, across the intestines and into draining lymph nodes (Table 1). 89,90 In addition, maternal sIgA alters the intestinal gene expression profile, especially those transcripts associated with enteritis in humans, and alleviates dextran-induced colonic mucosal damage.…”
Section: Gut Microbiome and Immune Effectsmentioning
confidence: 99%
“…Among infected individuals, evidence of ZIKV has been detected in serum, saliva, urine, semen, and breast milk [13, 1822]. Generally, transmission of antibodies through breast milk has been described, particularly for IgA, conferring passive immunity [23]. The presence of IgA, IgG, or IgM antibodies against similar flaviviruses such as West Nile Virus has been reported in breast milk [24].…”
Section: Introductionmentioning
confidence: 99%